On-farm testing of groundnut variety (Kadiri lepakshi K-1812) in semi-arid regions of Andhra Pradesh: ON-FARM TESTING OF GROUNDNUT VARIETY IN SEMI-ARID REGIONS OF ANDHRA PRADESH - JAYALAKSHMI M,; K RAGHAVENDRA CHOWDARY,; BH CHAITHANYA,; G PRASAD BABU, (Journal of Oilseeds Research, 2025)
On-farm testingwas conducted to evaluate the performance of the groundnut variety Kadiri Lepakshi (K-1812) during the kharif seasons of 2020 and 2021 in Kurnool district of Andhra Pradesh. Ten demonstrations were conducted each year with three groundnut varieties viz., Kadiri lepakashi (TO1), Nitya haritha (TO2) and K-6 (TO3) check variety. During two years of assessment, the pooled results revealed that the highest number of pods/plant was observed in Kadiri lepakshi variety (52.5) followed by Nitya haritha (47.5) and K-6 (39) varieties. The highest test weight (36.5 gm) and seed yield (3375 kg/ha) was also recorded in Kadiri lepakshi (K-1812) variety compared with Nitya haritha (2625 kg/ha) and K-6 varieties (2500 kg/ha). The per cent increase in yield was 28.5% and 35.1% higher in Kadiri lepakshi variety when compared with Nitya haritha and K-6 varieties respectively. The average highest net income (78395 `/ha) and benefit cost ratio (2.84) was realized in Kadiri lepakashi (K-1812). The lowest net income (65200 `/ha) and benefit cost ratio (1.90) was recorded in K-6 variety. The on farm trails have indicated that new variety lepakshi (K-1812) performed well over other two varieties.